Does a Payment-for-Outcomes Model Improve Indigenous Wellbeing? Commissioning Agencies and Social Impact Bonds in New Zealand - Humpage, Louise (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
Commissioning agencies and social impact bonds are two examples of New Zealand’s shift towards payment-for-outcomes funding mechanisms over the last decade, as the government attempted to improve both policy innovation and social outcomes. This article highlights that although the commissioning agencies have been more successful than social impact bonds, neither has completely achieved these goals of innovation and improved outcomes. This is particularly concerning given Indigenous Māori are disproportionately impacted by both policies. Discussion concludes by highlighting some of the problems associated with applying a payment-for-outcomes model to Indigenous Peoples, given these funding mechanisms are becoming increasingly popular in other settler nation states.